Italian Survey on Comparative Levofloxacin Susceptibility in 334 Clinical Isolates of Pseudomonas aeruginosa - Segatore, Bernardetta (American Society for Microbiology, 1999)
A national survey on susceptibility patterns of 334 Pseudomonas aeruginosa isolates from intensive care units and hematology and oncology wards from 13 Italian hospitals compared the in vitro activity of levofloxacin, an injectable oral fluoroquinolone, to those of ciprofloxacin, ofloxacin, ceftazidime, imipenem, amikacin, and gentamicin. Amikacin and imipenem had the best susceptibility profiles. The activity of levofloxacin was superior to those of the other quinolones and was comparable to that of ceftazidime. The effect of levofloxacin in vitro on P. aeruginosa clinical isolates suggests that further clinical investigations are warranted.